UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL BIJI EDAMAME (Glycin max (L) Merril) DENGAN METODE DPPH - Hadi Barru Hakam Fajar Siddiq, Rosida, Erika Fauziah Prabawati (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2016)
Antioxidants are compounds that can inhibit oxidation reactions with the free radicals and molecules are highly reactive. According to the previous research, edamame (Glycin max (L)Merril) plant is one of the plants that contains isoflavon compound that serves as an antioxidant. This study aims to determine the antioxidant activity of edamame extracts. This study is an experimental study. Edamame beans extract obtained by remaceration during 24 hours using 96% ethanol. The concentration of edamame beans extract were make different concentration from 90 ppm, 121,3 ppm, 143 ppm, 173,1 ppm. The extract then added with 0,02 g of DPPH free radicals that have been disolved in 100 mL of 96% ethanol. Those solutions were measured at wavelength 516,5 nm by an UV-Vis spectrophotometer. Vitamin C used as positive control. The result of Antioxidant activity of edamame beans extract has IC50value of 177,2 ppm and Vitamin C as a control has a IC50value 0,18 ppm.It means that 177,2 ppm of edamame beans extract classified as low antioxidant.Keywords : edamame beans (Glycin max L Merril, Antioxidant activity, DPPH method